DOES PROVIDING FREE ANTI-RETROVIRAL THERAPY ENSURE OPTIMAL ADHERENCE AMONG PEOPLE LIVING WITH HIV / AIDS? - Mallya, Sneha Deepak; Kamath, Veena Ganesh; Nair, Suma; Kamath, Asha (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Abstract Introduction/Back ground: Availability of Anti-Retroviral Therapy (ART) has revolutionalised the management of Human Immunodeficiency Virus /Acquired Immuno Deficiency Syndrome (HIV/AIDS) and improved the survival of those infected with the virus. However, adherence to therapy is a prerequisite for treatment success and preventing drug resistance. Aim: The present study was carried out with the aim of determining the level of adherence and factors affecting it among patients receiving free ART. Methods: A cross sectional study design was adopted and 320 HIV positive patients receiving free ART from a district hospital in Udupi were interviewed using a semi-structured questionnaire. Adherence to ART >95% of the prescribed medication was used as the cut off for deciding on the treatment adherence. Results: An encouragingly high 96.9% of the individuals were adherent to the medication over the past month. However, 41.8% of the participants reported to have ever missed doses of ART. On univariate analysis, having ever consumed alcohol, absence of side effects such as fatigue and tingling/numbness, having a feeling of sadness and sleep disturbances, being on Efavirenz based regimen, non-disclosure HIV status, being unsure of continuing lifelong treatment were significantly associated with non-adherence (p<0.05).Conclusion: Although non adherence was of concern among a small proportion of participants, a large number of them reported to have ever missed doses of ART. Â This finding suggests that adherence rate may be lower over longer periods of time. Hence, periodic assessments may address patient specific barriers and help to improve the adherence rate among this population.Â